2023
DOI: 10.7570/jomes23027
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Rich Food Intake Is Negatively Associated with Plasma Pentraxin 3 Levels

Asako Zempo-Miyaki,
Hiroshi Kumagai,
Koichiro Tanahashi
et al.

Abstract: Background: Levels of pentraxin 3 (PTX3), an anti-inflammatory cardioprotective protein, increase after weight loss in obese men and aerobic exercise in non-obese adults. However, the effect of nutritional characteristics on PTX3 levels remains unclear. This population-based, cross-sectional study investigated the association between circulating PTX3 levels and food intake in Japanese adults. Methods: We hypothesized that the consumption of high amounts of high-sugar foods would lead to low plasma PTX3 levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Calorie restriction was reported to increase the anti-inflammatory response. 25 Miyaki et al 26 also found that high sugar consumption was negatively associated with plasma PTX-3 level. In our study, it was found that increased dietary fat intake led to a decrease in PTX-3 levels, while increased PUFA intake led to an increase in plasma PTX-3 levels.…”
Section: Discussionmentioning
confidence: 92%
“…Calorie restriction was reported to increase the anti-inflammatory response. 25 Miyaki et al 26 also found that high sugar consumption was negatively associated with plasma PTX-3 level. In our study, it was found that increased dietary fat intake led to a decrease in PTX-3 levels, while increased PUFA intake led to an increase in plasma PTX-3 levels.…”
Section: Discussionmentioning
confidence: 92%